The Role of Social Capital in the Development of Fried Chicken Business - Ida Rosada; Farizah D Amran; Nurliani Nurliani; Rasmeidah Rasyid; Siti Hikmalia (Jurnal Manajemen Bisnis, 2023)
This study aims to describe the social capital owned by the owners, employees, and suppliers of raw materials for MSME fried chicken "Skripsi", analyze production and income, and business development. The research was conducted at the "Skripsi" Fried Chicken MSME, Jl. Abdullah Dg. Sirua. Informants (respondents) in this study were business owners, employees (who had worked for one year), and raw material suppliers, totaling ten people. This research is a case study using a qualitative approach and data collection techniques through observation, interviews, and documentation on the "Skripsi" fried chicken business. Data analysis used descriptive qualitative analysis and income analysis. The results of the study found that The social capital owned by the owners, employees, and suppliers of raw materials in the UMKM "Skripsi" fried chicken are: social norms, social networks, trust, cooperation, participation (participation), and reciprocity (reciprocity). Recapitulation of informants' responses to social capital with a weight value of 426 means that social capital plays a role in business development. MSME production and income Fried chicken "Skripsi" is profitable. The "Skripsi" fried chicken business is experiencing increasing development.